2018
DOI: 10.1021/acs.organomet.7b00836
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Stereoretentive Ruthenium Catalysts on the Basis of the M7 and the Ru–Benzylidene–Oxazinone Design

Abstract: A series of new stereoretentive ruthenium catalysts bearing the dithiocatecholate ligand was synthesiszed on the basis of the M7 and Ru–benzylidene–oxazinone design. The activity of the catalysts was tested in ring-opening cross-metathesis reactions, ring-closing metathesis reactions, cross-metathesis reactions, and self-metathesis reactions using Z- and E-configured starting materials. The desired metathesis products were obtained with moderate to high yields and with excellent stereoselectivities (>95%). Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…We were surprised by the very low activity of all new uNHC- and CAAC-based catalysts, whichwith the exception of Ru10 gave conversions below 40%. Despite the resulting E / Z stereoselectivity being very high in all cases ( E / Z = 5/95, which corresponds to the E / Z ratio of 4/96 reported for Ru4a in the literature), such low chemical activity seems to be disqualifying for practical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were surprised by the very low activity of all new uNHC- and CAAC-based catalysts, whichwith the exception of Ru10 gave conversions below 40%. Despite the resulting E / Z stereoselectivity being very high in all cases ( E / Z = 5/95, which corresponds to the E / Z ratio of 4/96 reported for Ru4a in the literature), such low chemical activity seems to be disqualifying for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“… a Conversion reported in the literature b Conversions were determined by GC with tetradecane used as an internal standard. …”
Section: Resultsmentioning
confidence: 99%
“…Variation of sterically demanding catecholthiolate ligands was reported by Grubbs in 2017 (e.g., Ru-11 ) [11]. In 2018 our group reported a series of electronically and sterically activated dithiolate ruthenium catalysts (e.g., Ru-12 ) [12]. However, none of these studies identified more efficient or practical catalysts compared to the ones shown in Fig.…”
Section: Reviewmentioning
confidence: 92%
“…To probe the impact of air on metathesis by the H 2 IPr and H 2 IMes derivatives Ru-2a / b , we first evaluated the impact of the atmosphere on representative reactions involving terminal or internal olefins under standard conditions . For the cross-metathesis of cis -1,4-butenediol with allylbenzene (Scheme a), yields after 4 h for reactions in THF in air were approximately half those obtained under inert atmosphere.…”
mentioning
confidence: 99%